Point-of-care ultrasound (POCUS) in acute hospitalized older patients focused on hydration - Hrabovsky, Vladimir; Skrobankova, Martina; Lys, Zdenek; Vrtkova, Adela; Spacilova, Veronika; Vaclavik, Jan (Biomedical papers, 2024)
Background. Acutely ill older patients frequently suffer not only from their acute disease, but also polymorbidity and frailty. Dehydration is another typical symptom, usually occurring in its both forms: low-intake dehydration and volume depletion. POCUS is goal-directed bedside ultrasound examination and several studies refer to its positive impact on hydration assessment. The aim of our study was to determine whether POCUS might influence (de)hydration diagnostics and/or treatments in older patients with acute illness. Methods. We randomized 120 acutely ill patients, aged ≥65 years, into POCUS and non-POCUS groups. All participants underwent routine laboratory tests, including haematocrit, serum and urine osmolality, blood urea nitrogen (BUN), creatinine, BUN/creatinine ratio, and C-reactive protein (CRP). POCUS was performed twice during the first two days to determine chest and abdominal status, with inferior vena cava (IVC) measurements. Length of hospital stay (HL) and consumption of infused fluids (CIF) was evaluated too. Data were analysed with exploratory methods and appropriate statistics. Results. Among all participants, the serum osmolality significantly correlated with age, BUN, creatinine and CIF. HL correlated with CRP and CIF. No significant correlations between IVC and other followed parameters were found. The POCUS group consumed significantly less infused fluids than the non-POCUS group, what could be influenced by POCUS examination of defined body compartments. Conclusion. Dehydration is a common feature in older individuals and its diagnostics is rather complicated. The role of POCUS in assessing hydration status remains unclear. However, our study showed, that ultrasound assessment provides next important information for comprehensive understanding of clinical status in older patients and can be beneficial for optimizing the treatment strategy, including fluid management decisions.
Keywords: point of care ultrasound; geriatrics; dehydration; volume depletion; inferior vena cava